Linker‐Region Modified Derivatives of the Deoxyhypusine Synthase Inhibitor CNI‐1493 Suppress HIV‐1 Replication. Issue 2 (3rd January 2016) - Schröder, Marcus; Kolodzik, Adrian; Windshügel, Björn; Krepstakies, Marcel; Priyadarshini, Poornima; Hartjen, Philip; van Lunzen, Jan; Rarey, Matthias; Hauber, Joachim; Meier, Chris
Abstract : The inhibition of cellular factors that are involved in viral replication may be an important alternative to the commonly used strategy of targeting viral enzymes. The guanylhydrazone CNI‐1493, a potent inhibitor of the deoxyhypusine synthase (DHS), prevents the activation of the cellular factor eIF‐5A and thereby suppresses HIV replication and a number of other diseases. Here, we report on the design, synthesis and biological evaluation of a series of CNI‐1493 analogues. The sebacoyl linker in CNI‐1493 was replaced by different alkyl or aryl dicarboxylic acids. Most of the tested derivatives suppress HIV‐1 replication efficiently in a dose‐dependent manner without showing toxic side effects. The unexpected antiviral activity of the rigid derivatives point to a second binding mode as previously assumed for CNI‐1493. Moreover, the chemical stability of CNI‐1493 was analysed, showing a successive hydrolysis of the imino bonds. By molecular dynamics simulations, the behaviour of the parent CNI‐1493 in solution and its interactions with DHS were investigated. Abstract : A series of linker‐modified derivatives of CNI‐1493, a known inhibitor of deoxyhypusine synthase (DHS), are synthesized and tested for their antiviral potency. Even compounds that are unable to adopt the 'sandwich‐like' conformation found in a recent co‐crystal structure of CNI‐1493 and DHS showed potent activity against HIV‐1 replication, pointing to a different binding mode of the inhibitors and DHS.